Applications of modern RF photonics - Devgan, Preetpaul Singh (Artech House applied photonics series., 2018)
This unique new resource presents applications of modern RF photonic systems that use RF photonic components for commonly used signal processing systems. This book provides insight into how a variety of systems work together, including RF down conversion, analog to digital conversion, RF oscillators, and frequency identification. A comparison of analog versus digital systems is presented. Readers find in-depth coverage of analog delay lines using RF photonics, various system architectures, and details about RF photonic component performance. Signal processing utilizing RF photonics and the need for down conversion is discussed. The many advancements in analog delay line performance are explained, including those in photodetector, optical fibers, and optical and amplifier modulators. The book highlights the advantages of using oscillators utilizing RF photonics and explores the elements of phase noise, timing jitter, and optoelectronic oscillators. The benefits of signal identification, isolation, and separation of RF photonics are identified. Professionals are brought up to speed on RF frequency identification using optical injection locking. The book provides discussions on the fundamentals and advancements in integrated RF photonics and explains how to design an RF photonic downconverter. It covers additional applications of integrated photonic circuits and gives an explanation of why to use different modulation formats for different applications.